2021
DOI: 10.32672/jse.v6i3.3119
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor yang Mempengaruhi Kejadian Stunting pada Anak: Studi Literatur

Abstract: Stunting is a global health problem  and in Indonesia, both in urban and rural areas. Stunting occurs in children and if preventive actions  are not taken such as nutrition, immunization, and maintain a clean environment, it may  cause disturbances in children  in brain development, body metabolism, and physical growth. Risk factors for stunting in children’s  parental habits , basic immunization, basic sanitation, history of infectious diseases, smoking habits, and upper respiratory tract infections. The purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 11 publications
0
4
0
5
Order By: Relevance
“…Faktor tidak langsung meliputi pola asuh ibu, kerawanan pangan keluarga, pelayanan kesehatan lingkungan, sumber air bersih, dan sanitasi layak (Martony, 2023;Khoiriyah & Ismarwati, 2023 ;Sarwani Sri Rejeki et al, 2022 ;Zairinayati & Purnama, 2019). Selain itu, stunting juga terjadi karena adanya interaksi dan kontribusi dari berbagai faktor meliputi akses terhadap masalah kesehatan yang memadai, kondisi ekonomi keluarga yang buruk, serta faktor-faktor sosial, budaya, ekonomi, dan politik (Mashar et al, 2021).…”
Section: Pendahuluanunclassified
“…Faktor tidak langsung meliputi pola asuh ibu, kerawanan pangan keluarga, pelayanan kesehatan lingkungan, sumber air bersih, dan sanitasi layak (Martony, 2023;Khoiriyah & Ismarwati, 2023 ;Sarwani Sri Rejeki et al, 2022 ;Zairinayati & Purnama, 2019). Selain itu, stunting juga terjadi karena adanya interaksi dan kontribusi dari berbagai faktor meliputi akses terhadap masalah kesehatan yang memadai, kondisi ekonomi keluarga yang buruk, serta faktor-faktor sosial, budaya, ekonomi, dan politik (Mashar et al, 2021).…”
Section: Pendahuluanunclassified
“…Immunization with haram and/or unclean things is permitted provided that it is carried out in an emergency condition, if there is no halal and holy vaccine, and there must be competent medical personnel. 13 The result of this belief is that many husbands forbid their wives to go to immunize their children. In addition, the distance of the health center is far, so many mothers cannot take their children to immunization because of limited vehicles.…”
Section: Humanmentioning
confidence: 99%
“…Incomplete immunization for toddlers causes toddlers' immunity to become weak, making them susceptible to infection. 13,[19][20][21][22][23] Research in Banda Aceh district also showed that stunting was caused by incomplete immunization. The risk of stunting increased 4 times greater in children under five who were not fully immunized.…”
Section: Humanmentioning
confidence: 99%
“…As a result of this habit, cigarette smoke exposure has a direct impact on the growth and development of the children by interfering the absorption of nutrients which will later disrupt their growth and development (Mashar, 2021). The adults' habit of consuming cigarettes will cause children to experience infections because they are exposed to dangerous chemical substances from cigarettes and will inhibit children's growth (Sari & Resiyanthi, 2020), apart from that, cigarette smoke exposure is one of the major problems that causes stunting in children due to the chemicals generated.…”
Section: Introductionmentioning
confidence: 99%